Traffic Directorate Efforts Through Electronic Traffic Law Enforcement (E-TLE) in Law Enforcement for Traffic Violators at the DIY Regional Police - Angger Gangga Mahendra (Advances in Police Science Research Journal, 2021)
Penilangan is one of the main tasks of the traffic police in law enforcement efforts against the community. Along with the development of information technology, an electronic ticketing innovation emerged called Electronic Traffic Law Enforcement (E-TLE). This study describes the process of implementing E-TLE, identifying the supporting factors for implementing E-TLE, and knowing the efforts to increase the role and avoid obstacles in the implementation of E-TLE by Ditlantas Polda DIY. This research uses a qualitative case study approach. The selection of the research location at Ditlantas Polda DIY was based on purposive sampling with the consideration of the Polda who had implemented E-TLE so that it could be evaluated. Sources of data include primary data obtained from interviews and observations and secondary data obtained from document analysis. From this research, it is hoped that there will be an increase in facilities and infrastructure, an increase in the quality and quantity of personnel, and an increase in service to the community.